1995
DOI: 10.1007/bf00593380
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from primary deep cerebral venous sinus thrombosis with recanalisation

Abstract: A 50-year-old woman with idiopathic deep cerebral sinus and vein thrombosis (DCVT) had cerebellar disturbance prior to impaired consciousness. CT and MRI revealed haemorrhagic infarction in the cerebellum and signal changes suggesting infarction in the thalamus and basal ganglia bilaterally. The straight sinus and internal cerebral vein (ICV) were dense on CT. On angiography, the vein of Galen (VG) and straight sinus were not seen. Following clinical recovery, CT and MRI became normal, and angiography showed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…With regard to DVT, an attenuated vein sign has been described in several case reports, 13,[30][31][32][33] but its diagnostic value has never been assessed systematically. Here, we demonstrated that NCCT is very helpful in the diagnosis of DVT, as the attenuated vein sign shows both a high sensitivity and a high specificity for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to DVT, an attenuated vein sign has been described in several case reports, 13,[30][31][32][33] but its diagnostic value has never been assessed systematically. Here, we demonstrated that NCCT is very helpful in the diagnosis of DVT, as the attenuated vein sign shows both a high sensitivity and a high specificity for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68][69][70] Pharmacological local thrombolysis is performed at our institution if the patient is in coma at the outset or if there is clinical deterioration despite full anticoagulation. Currently local thrombolysis of the cerebral venous sinuses is usually performed via the transvenous femoral route in an anaesthetised patient (fig 9).…”
Section: Cerebral Venous Sinus Thrombosismentioning
confidence: 99%